Synthesis of hierarchical porous zinc oxide (ZnO) microspheres with highly efficient adsorption of Congo red - Lei, Chunsheng; Pi, Meng; Jiang, Chuanjia; Cheng, Bei; Yu, Jiaguo (Journal of colloid and interface science, 2017)
[Display omitted] Hierarchical porous zinc oxide (ZnO) was successfully synthesized via a facile hydrothermal method followed by calcination, and characterized by X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscopy, nitrogen adsorption–desorption, and Fourier transform infrared spectroscopy analyses. The as-prepared porous ZnO exhibits microsphere morphologies with diameters of 6–8μm, which are assembled from two-dimensional nanosheets. The as-prepared hierarchical porous ZnO microspheres possessed high specific surface areas (57m2/g), and were evaluated for adsorption of Congo red (CR) in aqueous solution. The adsorption kinetics data were described by the pseudo-second-order kinetics and intraparticle diffusion models, while the equilibrium adsorption data were well fitted to the Langmuir model, with a maximum adsorption amount of 334mg/g. The as-prepared hierarchical porous ZnO exhibited higher CR adsorption capacity than commercial ZnO and various other materials, and thus could be an effective adsorbent for removal of anionic organic dyes from wastewater.